Lactate, a useful marker for disease mortality and severity but an unreliable marker of tissue hypoxia/hypoperfusion in critically ill patients - Shigeki Kushimoto; Satoshi Akaishi; Takeaki Sato; Ryosuke Nomura; Motoo Fujita; Daisuke Kudo; Yu Kawazoe; Yoshitaro Yoshida; Noriko Miyagawa (Acute Medicine & Surgery, 2016)
Early aggressive hemodynamic resuscitation using elevated plasma lactate as a marker is an essential component of managing critically ill patients. Therefore, measurement of blood lactate is recommended to stratify patients based on the need for fluid resuscitation and the risks of multiple organ dysfunction syndrome and death. Hyperlactatemia is common among critically ill patients, and lactate levels and their trend may be reliable markers of illness severity and mortality. Although hyperlactatemia has been widely recognized as a marker of tissue hypoxia/hypoperfusion, it can also result from increased or accelerated aerobic glycolysis during the stress response. Additionally, lactate may represent an important energy source for patients in critical condition. Despite its inherent complexity, the current simplified view of hyperlactatemia is that it reflects the presence of global tissue hypoxia/hypoperfusion with anaerobic glycolysis. This review of hyperlactatemia in critically ill patients focuses on its pathophysiological aspects and recent clinical approaches. Hyperlactatemia in critically ill patients must be considered to be related to tissue hypoxia/hypoperfusion. Therefore, appropriate hemodynamic resuscitation is required to correct the pathological condition immediately. However, hyperlactatemia can also result from aerobic glycolysis, unrelated to tissue dysoxia, which is unlikely to respond to increases in systemic oxygen delivery. Because hyperlactatemia may be simultaneously related to, and unrelated to, tissue hypoxia, physicians should recognize that resuscitation to normalize plasma lactate levels could be over‐resuscitation and may worsen the physiological status. Lactate is a reliable indicator of sepsis severity and a marker of resuscitation; however, it is an unreliable marker of tissue hypoxia/hypoperfusion.